Repurchase Premia as a Reason for Dividends: A Dynamic Model of Corporate Payout Policies - Chowdhry, Bhagwan; Nanda, Vikram (Review of Financial Studies, 1994)
We propose that it is precisely because firms’ repurchases of their own stock through tender offers are associated with large stock-price increases that repurchases are unattractive as a means of distributing cash. As a result, firms distribute some cash in the form of dividends—despite the tax disadvantage—and carry the rest to future periods. However, when their stock is sufficiently undervalued, firms distribute all accumulated cash through stock repurchases. We show that dividends are smoothed and are positively related both to earnings innovations and to previous period’s dividends. Also, the stock-price reaction to a repurchase announcement, of a given size, is increasing in the previous period’s dividends.